What a scientist looks like: Portraying gender in the scientific media - Becky Loverock; Miranda M. Hart (Canadian Science Publishing, 2018)
How men and women are portrayed in the media informs societal attitudes towards gender. Although this is true for all media, the scientific media has received little scrutiny, despite known gender biases inherent in scientific culture. We asked whether the top scientific journals, Nature and Science, represented men and women equally as authors, subjects, and objects in photographs. Overwhelmingly, women were underrepresented in these magazines, an effect that was apparent even in advertisements and stock photographs. Clearly, gender bias in science exists at many levels.